From Zero to Launch: Roadmap Praktis Memulai Bisnis - Qaulan Tsaqila Kamaruddin; Farida Febriati (Abdimas Awang Long, 2026)
In the digital era, many aspiring entrepreneurs face various challenges when starting a business, such as limited capital, lack of basic knowledge, and fear of failure. This community service activity aims to develop and provide a practical roadmap for beginner entrepreneurs, guiding them from zero to product launch in order to support systematic planning and business execution. Throughout the implementation of this program, participants showed high enthusiasm in following the presentations delivered by the speakers. The results of this activity indicate that the participants gained a better understanding of the practical steps to start a business, including the application of the Business Model Canvas to develop an initial business model. The provided roadmap is expected to enhance readiness, reduce risks, and support the success of new ventures from the early stages until the product or business is ready for launch.